Rattus korinchi Robinson and Kloss 1916 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus korinchi Robinson and Kloss 1916 Rattus korinchi Robinson and Kloss 1916, J. Str. Br. Roy. Asiat. Soc., 73: 275. Type Locality: Indonesia, W Sumatra, Propinsi Jambi, Gunung Kerinci, Sungai Kring, 7300 ft (2225 m). Vernacular Names: Sumatran Mountain Rat. Distribution: Recorded only from Gunung Kerinci and Gunung Talakmau in W Sumatra (Musser, 1986:4). Conservation: IUCN – Lower Risk (lc). Discussion: Rattus species group unresolved. Revised by Musser (1986). Represented by very few specimens, and morphologically unlike any other described species of Rattus . Member of the cluster of murine species endemic to Sumatra (Musser, 1986; see also account of Maxomys hylomyoides ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1472, DOI: 10.5281/zenodo.7316535